Tracking Rural Change Community, Policy and Technology in Australia, New Zealand and Europe - Merlan, Francesca (ANU Press, 2009)
A key, intensifying change affecting rural areas in the last few decades has been a decline in the proportion of national populations whose principal livelihood is farming. The corresponding re-distribution of population has typically resulted in a net population loss to rural areas, and diversification of rural activity. The corporatization and technological modification of food production has prompted new policy challenges, and has bound rural and urban populations together in new relationships articulated in moral discourses of custodianship, food safety, and sustainability. Contributors to this volume came together in the attempt to stimulate collective insight into trends of rural change in Australia, New Zealand and Europe. The first two countries have been characterised by avowedly `neoliberal' rural policy - with considerable departures from it in practice; Europe, on the other hand, by a mix of policy measures which attempt to integrate land management and sustainability, diversification and maintenance of a competitive farming sector within an overarching policy framework more overtly, though only partially, oriented towards sustaining rural society. Aiming to build on research relating to the character of rural transitions, this volume offers substantive and critical contributions to the understanding of the sources of unpredictability, instability, and continuity, that underpin rural transition. The papers explore changes and continuities in policy, the governance of rural spaces, technological developments relating to rural areas and populations, and social forms of subjectivation and participation in increasingly diverse rural settings.